Az Erdélyi Református Egyházkerület álláspontja az 1850-es évek Pátens-harca idején - Olga LUKÁCS (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2025)
Contributions to the History of the Forced State Church in the 1850s. Through a decree issued in 1849 and subsequently in the early 1850s, Haynau prohibited ecclesiastical assemblies throughout the territory of Hungary, thereby rendering church administration – founded on collegial governance – and the internal structure of the Protestant churches unworkable. With these decrees, he clearly anticipated a form of coerced state church system, which had been the deliberate direction of counter-revolutionary absolutism’s anti-Protestant ecclesiastical policy from the outset. Minister Leo Thun sought to establish an imperial church organization encompassing all Protestant churches within the empire (including the Unitarian Church), with a common imperial synod at its centre.